2009
DOI: 10.3814/2009/979318
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Human Acute Myocardial Infarction: The Rationale for Clinical Trials of Apoptosis Inhibition in Acute Myocardial Infarction

Abstract: The objective of the present review was to examine apoptosis in patients with acute myocardial infarction (MI) and to address (i) the prevalence of apoptosis in acute MI, (ii) techniques to determine apoptosis, (iii) time period from the onset of acute MI to the detection of apoptosis, (iv) criticisms about apoptosis in acute MI. A systematic literature search identified over 20 publications comprising over 400 patients. The prevalence of apoptosis varied from over 90% in nuclear imaging studies using annexin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…To support the results of TUNEL staining, the amount of cleaved caspase-3 was assessed by immunohistochemistry [ 26 , 27 ] ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To support the results of TUNEL staining, the amount of cleaved caspase-3 was assessed by immunohistochemistry [ 26 , 27 ] ( Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To support the results of the TUNEL staining, the amount of cleaved casapse-3 was assessed by immunohistochemistry ( Fig. 4 ) ( 19 , 20 ). In the apoptotic pathways, cleaved caspase-3 (the active form of the caspase) is derived from procaspase-3 by the removal of prodomain.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that HS or high sodium in the body would affect cardiovascular systems via RAS pathways. 39,40 Thus, we measured key components of the systemic RAS in the offspring exposed to prenatal HS. The data showed that plasma angiotensin II and ACE levels were reduced only in the newborn exposed to prenatal HS; however, this reduction was back to normal in the 1-month old or 5-month old.…”
Section: Discussionmentioning
confidence: 99%